2023
DOI: 10.1001/jamanetworkopen.2023.39793
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Staphylococcus aureus Infections in Patients With and Without Preoperative Colonization

Darren P. R. Troeman,
Derek Hazard,
Leen Timbermont
et al.

Abstract: ImportanceStaphylococcus aureus surgical site infections (SSIs) and bloodstream infections (BSIs) are important complications of surgical procedures for which prevention remains suboptimal. Contemporary data on the incidence of and etiologic factors for these infections are needed to support the development of improved preventive strategies.ObjectivesTo assess the occurrence of postoperative S aureus SSIs and BSIs and quantify its association with patient-related and contextual factors.Design, Setting, and Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…MDR means resistance to more than three different antibiotic classes. Characterized by potential drug resistance mechanisms, these bacteria may cause life-threatening infections among immunocompromised or critically ill patients, especially diabetics [8,9]. This is because diabetic patients have a higher risk of developing chronic ulcers that lower the quality of life and have a significant impact on the healthcare system [10].…”
Section: Introductionmentioning
confidence: 99%
“…MDR means resistance to more than three different antibiotic classes. Characterized by potential drug resistance mechanisms, these bacteria may cause life-threatening infections among immunocompromised or critically ill patients, especially diabetics [8,9]. This is because diabetic patients have a higher risk of developing chronic ulcers that lower the quality of life and have a significant impact on the healthcare system [10].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the combination of NPWT and silver nanoparticle sheets proves a synergistic and beneficial effect on wound healing and graft integration. As Khansa et al reported, infected diabetic foot ulcers were proven to heal more quickly with the use of silver-coated sponges instead of plain ones, as they reduce the bacterial growth of biofilm-causing species (Pseudomonas aeruginosa and Staphylococcus aureus, even MRSA) [42,43]. The synergistic effects of silver and NPWT can be achieved by applying a silver layer underneath a standard polyurethane sponge or by utilizing a polyurethane sponge coated with silver [44].…”
Section: Discussionmentioning
confidence: 99%
“…We present a series of cases of C. auris infections and/or colonization, reported from October 2022 to July 2023 in a public university hospital in Bucharest, mainly in the cardiovascular surgery (CVS)-associated intensive care unit (ICU). Patients who underwent surgical procedures were screened for Methicillin-resistant Staphylococcus aureus and received perioperative antibiotic prophylaxis [22]. Of the 21 reported cases with C. auris during this period, some were isolated cases-in different departments-and others met the case definition for an outbreak diagnosed during the hospitalization (Figures 1a,b and 2a,b).…”
Section: Case Series Descriptionmentioning
confidence: 99%